PERANAN EXECUTIVE HOUSEKEEPER PADA HOTEL PUSAKO BUKITTINGGI - Yolveri Yolveri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This Research the role of the executive housekeeper in improving the quality of hotel housekeeping services. In improving the quality of housekeeping services, Executive Housekeeper Hotel Pusako Bukittinggi has several roles and constraints that must be controlled when carrying out work so that it will affect the level of service and progress of a hotel. This research uses data collection methods by observation, interview and literature study. The data obtained were then analyzed and presented in a qualitative method. In improving the quality of housekeeping services in a hotel, Executive Housekeeper has a role as Public Relations, Interdepartmental Relations, Security, Quality Control, Motivator and Leader in order to carry out the responsibilities of supervising, running, and controlling all subordinate work for smooth housekeeping. The results showed that in their duties, the Executive Housekeeper of Pusako Bukittinggi Hotel was unable to perform its role optimally due to various obstacles. The constraints faced by the Executive Housekeeper are the frequent lack of procurement of goods for the room, late check-out, the lack of Roomboy Staff that can hinder the work of Executive Housekeepers and an Executive Housekeeper who lacks knowledge of housekeeping and this is the main thing that becomes a major obstacle for Executive Housekeeper and so on . With these various obstacles can hamper the improvement in the quality of hotel housekeeping services. To improve housekeeping services, hotel management must pay attention in appointing someone to be an Executive Housekeeper in accordance with their criteria and providing solutions to existing constraints, so that the Executive Housekeeper can work in accordance with his role.